Adherence to preventive measures after splenectomy in the hospital setting and in the community - Hélène Coignard-Biehler; Fanny Lanternier; Arnaud Hot; Dominique Salmon; Anne Berger; Marianne de Montalembert; Felipe Suarez; Odile Launay; Marc Lecuit; Olivier Lortholary (Elsevier, 2011)
Summary: Overwhelming post-splenectomy infection (OPSI) remains a long-term risk in asplenic patients, which may be reduced by appropriate preventive measures. Specific guidelines have been developed to lower its incidence. Aims: To assess the implementation of guidelines by specialized physicians of a university hospital and primary care physicians. Methods: A retrospective review of splenectomized patients' medical files over a six year period was carried out. Patients' general practitioners were contacted and a questionnaire was sent to them. Results: 154 individuals who underwent splenectomy between 2000 and 2005 were eligible (62 children and 92 adults): 70.8% received pneumococcal vaccine, 44% received vaccine against Haemophilus influenzae type b with a good cover of children population (88.7%), 24% received meningococcal vaccine. Prophylactic antibiotics were prescribed in 74% of patients. Septic events were found in 8.4%, and global mortality was 11.7% during a mean follow-up period of 4.5 years. Conclusions: Management of the infectious risk in asplenic patient has to be improved: some of the patients are not correctly identified as at risk of OPSI, and vaccination against Neisseria meningitidis is insufficient. Hospital specialists should improve the implementation of guidelines and give better information to general practitioners involved. Keywords: Prevention, Infection, Splenectomy, Immunization